Mitigating externalities of terrorism on tourism: Global evidence from police, security officers and armed service personnel - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2018)
In this paper, we investigate the role of security officers, the police and armed service personnel in dampening the effect of terrorism externalities on tourist arrivals. The temporal and geographic scopes are respectively 2010-2015 and 163 countries. Four terrorism measurements are used. They include the number of: incidents, injuries, fatalities and property damages. The main findings indicate that armed service personnel can effectively be used to modulate the damaging influence of all four terrorism externalities in order to achieve a positive net effect on tourist arrivals. Conversely, the corresponding moderating role of security officers and the police is not statistically significant. Moreover, violent demonstrations and homicides have a harmful effect on tourist arrivals while the number of incarcerations displays the opposite effect. Policy implications are discussed.
Keywords: D74; Z32; Z38; 330; Terrorism; Peace; Tourism